Involvement of extracellular matrix proteins in the course of experimental paracoccidioidomycosis (2008)
ABSTRACT : We aimed at determining involvement of extracellular matrix proteins (ECMp) and an ECM-binding adhesin (32-kDa protein) from Paracoccidioides brasiliensis, in the course of experimental paracoccidioidomycosis. BALB/c mice were infected with P. brasiliensis conidia previously incubated with soluble laminin, fibronectin and fibrinogen or a mAb against the fungal adhesin. Inflammatory response, chitin levels and cytokine production at different postinfection periods were determined. Chitin was significantly decreased in lungs of mice infected with ECMp-treated conidia when compared with controls at week 8, especially with laminin and fibrinogen. Contrariwise, when animals were infected with mAb-treated conidia no differences in chitin content were found. The observed inflammatory reaction in lungs was equivalent in all cases. IFN-g increased significantly in lungs from mice infected with soluble ECMp – (at day 4 and week 12) or mAb-treated conidia (at week 12) when compared with animals infected with untreated conidia. Significant increased levels of tumour necrosis factor-a were observed at 8 weeks in animals infected with ECMp-treated conidia while no differences were observed during the remaining periods. These findings point toward an inhibitory effect of ECMp on P. brasiliensis conidia infectivity and suggest that these proteins may interfere with conidia initial adhesion to host tissues probably modulating the immune response in paracoccidioidomycosis.